Turia : a Roman woman's Civil War - Osgood, Josiah, 1974- (Women in antiquity., 2014)
"The civil wars that brought down the Roman Republic were fought on more than battlefields. Armed gangs infested the Italian countryside, in the city of Rome mansions were besieged, and bounty-hunters searched the streets for 'public enemies.' Among the astonishing stories to survive from these years is that of a young woman whose parents were killed, on the eve of her wedding, in the violence engulfing Italy. While her future husband fought overseas, she staved off a run on her father's estate. Despite an acute currency shortage, she raised money to help her fiancé in exile. And when several years later, her husband, back in Rome, was declared an outlaw, she successfully hid him, worked for his pardon, and joined other Roman women in staging a public protest. The wife's tale is known only because her husband had inscribed on large slabs of marble the elaborate eulogy he gave at her funeral. Though no name is given on the inscriptions, starting as early as the seventeenth century, scholars saw similarities between the contents of the inscription and the story, preserved in literary sources, of one Turia, the wife of Quintus Lucretius. Although the identification remains uncertain, and in spite of the other substantial gaps in the text of the speech, the 'Funeral Speech for Turia' (Laudatio Turiae), as it is still conventionally called, offers an extraordinary window into the life of a high-ranking woman at a critical moment of Roman history. In this book Josiah Osgood reconstructs the wife's life more fully than it has been before by bringing in alongside the eulogy stories of other Roman women who also contributed to their families' survival while working to end civil war. He shows too how Turia's story sheds rare light on the more hidden problems of everyday life for Romans, including a high number of childless marriages. Written with a general audience in mind, Turia : A Roman Woman's Civil War will appeal to those interested in Roman history as well as war, and the ways that war upsets society's power structures. Not only does the study come to terms with the distinctive experience of a larger group of Roman women, including the prudence they had to show to succeed, but also introduces readers to an extraordinary tribute to married love which, though from another world, speaks to us today"--